Daisy's perfect word - Feder, Sandra V. 1963- (Kids Can Press, 2012)
"Curly-haired Daisy likes picking lemons on sunny days, playing kickball and making long dandelion chains. But more than any of these things, she loves words and even compiles lists of her favorites in a bright green notebook covered with purple polka dots. When Daisy's beloved teacher, Miss Goldner, becomes engaged and must move to another town, Daisy decides to give her the ultimate gift: the perfect word. But with so many good words to choose from, finding just the right one isn't easy." - Amazon